الشيخ العربي العوني وجهوده في الدعوة والتعليم ببلدة سيدي عون وما حولها - صغيري, سفيان (جامعة الوادي - University of Eloued, 2023)
برز العديد من شيوخ العلم والصلاح في واد سوف، حواضرها وبواديها من خلال جهودهم في الدعوة والتعليم، لكنهم للأسف عاشوا في الظل وماتوا تحت الظل، ولم يُعْرفوا الا في ذاكرة تلاميذهم ومن عايشهم في مجالهم الضيق، منهم الشيخ العربي العوني، الذي برز في جهوده الدعوية في التربية والتعليم ببلدة سيدي عون، خلال الفترة التي قضاها فيها. وهدفنا في هذه المقالة هو التعريف بهذه الشخصية العلمية والدينية المغمورة، وتبيان دورها الكبير في نشر التعليم العربي الأصلي في وسط سكان المنطقة وما حولها، التي كان يسودها الجهل والفقر جراء السياسة الاستعمارية، والدعوة الى مواجهة الاستعمار بالعلم والعمل، من خلال المحاضرات والدروس التي كان يلقيها في مسجدها العتيق وخارجه، حتى هجرته الى تونس مخلفا وراءه ثلة من تلاميذه الذين واصلوا في جهودهم التعليمية حتى تحقق الاستقلال. Many Sheikhs of science and goodness have emerged in Oued-Souf, Its cities and valleys through their efforts The Da'wa And The Education, But unfortunately, they lived in the shadows and died under the shadows, And they only knew in the memory of their pupils and those who lived in their narrow field, Them Sheikh Al Arabi Al-Ouni, who has emerged in his reform efforts in education in Sidi- Aoun, During his time before the Starting in. Our objectives in this article is to introduce this unknown scientific and religious –but Not Famous–, And to show its great role in spreading the original Arabic education among the population of the region and nearby, where ignorance and poverty were widespread because of colonial politics, Through the lectures and lessons he gave in her ancient mosque and outside, Until he emigrated to Tunisia, leaving behind a group of his students who continued their educational efforts until independence was achieved
Cheikh Al Arabi Al-ouni And His Efforts The Da'wa And The Education In Sidi Aoun And Nearby
مقال
Keywords: العربي العوني؛ سيدي عون؛ التعليم؛ الدعوة؛ علماء سوف